If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 3x = -2 Solving 10 + 3x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -2 + -10 3x = -2 + -10 Combine like terms: -2 + -10 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 2*2+2= | | 4c^3-16c^2+12c=0 | | (x*13.8985-1387.07)+(x*707.096-13081.276)=0 | | 36x^2-9y^2= | | 15ab+2a=0 | | 2+3*5-8= | | 13x-7.(x-2)=44 | | 9x^2-4= | | 2x+4(16+x)=40 | | 6-x=3 | | 5+8x=20+2x | | 8(2t+1)=4(7t+7) | | 2x+4(16-x)=40 | | 0.075(x+2000)=0.08x+0.06(2000) | | X^2-36= | | .3x+.12=3.72 | | 3x-6y-2=16 | | 3t^2-48t+180=0 | | 9-26x=36 | | y-6=-25 | | 1/7(3y+2)=2+1/3(y+2) | | 3x-6y+2=16 | | 3y-6x+2=16 | | 5(x-3)=-40 | | -26-15x=19 | | 5x^2+2x-9=0 | | 2x=3x+5+865 | | -15x-26=19 | | (7z-3)(z+5)-(7z-3)(z-4)= | | 5t-2t=16 | | x*5+250=x*15-10 | | 4=18+x |